1699. Variation of antimicrobial resistance by age groups for outpatient UTI isolates in US females: A multicenter evaluation from 2011 to 2019. (31st December 2020) - Kaye, Keith S; Gupta, Vikas; Mulgirigama, Aruni; Joshi, Ashish V; Scangarella-Oman, Nicole; Yu, Kalvin; Ye, Gang; Mitrani-Gold, Fanny S
Abstract: Background: An estimated 12% of women experience ≥ 1 episode of urinary tract infection (UTI) annually. Incidence is bimodal, with peaks occurring in young, sexually active women (18–24 years) and in post-menopausal women. Previous studies suggest the prevalence of antimicrobial resistance (AMR) in UTI is rising; however recent AMR data for community-acquired UTI are lacking. We estimated the prevalence of AMR among US females with outpatient UTI in 2011–2019, stratified by age. Methods: A retrospective, multicenter, cohort study of AMR among non-duplicate urine isolates in US females (≥ 12 years of age) from 296 institutions from 2011–2019 (BD Insights Research Database, Franklin Lakes, NJ). Phenotypes examined for Enterobacterales (ENT) were: extended spectrum β-lactamase positive (ESBL+; determined by commercial panels or intermediate/resistant to ceftriaxone, cefotaxime, ceftazidime or cefepime); nitrofurantoin (NFT) not-susceptible (NS); fluoroquinolone (FQ) NS; trimethoprim-sulfamethoxazole (TMP-SMX) NS; and NS to ≥ 2 or ≥ 3 drug classes (including ESBL+). Gram-positive phenotypes were, methicillin resistant S. aureus and S. saprophyticus and vancomycin-resistant Enterococcus . Isolates were stratified by patient age (≥ 12 to < 18, ≥ 18 to < 55, ≥ 55 to < 65, ≥ 65 to < 75, ≥ 75 years). Chi-square tests were used to evaluate AMR difference between groups. Results: In total, urine isolates were collected from 106 to 296 (2011–2019) US sites. Overall, the prevalence of antimicrobial NS increased with age for all E. coli phenotypes (all P< 0.001; Table 1), and for non- E. coli ENT (all P< 0.001), except NFT NS, which decreased from 70.6% to 59.7% (P=0.002; Table 2). The greatest difference between age groups in prevalence of resistance was observed for FQ NS E.coli : 5.8% (≥ 12 to < 18 years) vs 34.5% (≥ 75 years). For the multi-drug resistant E. coli phenotypes, resistance increased with age, ranging from 4.8–22.4% and 0.9–6.5% for ≥ 2 and ≥ 3 drug NS, respectively. Overall, the prevalence of resistance for Gram-positive phenotypes increased with age (all P< 0.001; Table 3). Table 1. Prevalence of antimicrobial resistance among E. coli isolates in US females with outpatient UTI by age group. Table 2. Prevalence of antimicrobial resistance among non-E. coli ENT isolates in US females with outpatient UTI by age group. Table 3. Prevalence of antimicrobial resistance among Gram-positive isolates in US females with outpatient UTI by age group. Conclusion: The prevalence of AMR in E. coli and non- E. coli ENT increased with age among US females presenting for care in the outpatient setting overall. A similar trend increase by age is also seen in Gram-positive isolates. Disclosures: Vikas Gupta, PharmD, BCPS, Becton, Dickinson and Company (Employee, Shareholder)GlaxoSmithKline plc. (Other Financial or Material Support, Funding) Aruni Mulgirigama, MBBS, GlaxoSmithKline plc. (Employee, Shareholder) Ashish V. Joshi, PhD, GlaxoSmithKline plc. (Employee, Shareholder) Nicole Scangarella-Oman, MS, GlaxoSmithKline plc. (Employee, Shareholder) Kalvin Yu, MD, Becton, Dickinson and Company (Employee)GlaxoSmithKline plc. (Other Financial or Material Support, Funding) Gang Ye, PhD, Becton, Dickinson and Company (Employee)GlaxoSmithKline plc. (Other Financial or Material Support, Funding) Fanny S. Mitrani-Gold, MPH, GlaxoSmithKline plc. (Employee, Shareholder)